The Erasure of Women's Activism in Nora Twomey's The Breadwinner - Clough, Kimberly (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2025)
The return of Taliban rule in Afghanistan has renewed interest in The Breadwinner, the story of Parvana, an eleven-year-old girl who passes as a boy to provide for her family after the Taliban abducts her father. Set in Kabul on the cusp of 9/11, the celebrated children’s novel (2000), written by Deborah Ellis, found great success in Nora Twomey’s animated adaptation (2017), which was nominated for Best Animated Feature at the 90th Academy Awards. Using animation conventions to build on the cultural sensitivity and accuracy present in the book, the film addresses global concerns arising after the novel’s publication. Although critics have lauded the film as feminist, the adaptation excises Ellis’s focus on Afghan women’s activism and replaces this community with characters who are men. These added characters provide a stronger narrative structure than the novel and successfully humanize Taliban members; however, this is at the expense of representing women’s communal action. As a result, Afghan women are portrayed as isolated and helpless; this representation contradicts the film’s pacifist messages by implying that western military intervention is necessary. Due to its prevalence in curricula, the film is in danger of perpetuating the myth that an individual alone can alter their circumstances rather than recognizing that the feminist collective is necessary for widespread and sustained change. I argue that the representation of activist groups already present in Kabul that Ellis’s texts gestures to are erased by the animated adaptation’s focus on male characters.